Determination of gonad reproductive state using non-lethal ultrasonography in endangered black (Haliotis cracherodii) and white abalone (H. sorenseni) - Boles, Sara E.; Rogers-Bennett, Laura; Bragg, Wendy K.; Bredvik-Curran, Jessica; Graham, Suzanne; Gross, Jackson A. (Frontiers in Marine Science, 2023)
Populations of California abalone (Haliotis spps.) were once abundant; however, due to historic overharvesting, disease, kelp forest decline, and habitat degradation all of these species have declined dramatically. Today, the black (H. cracherodii) and the white abalone (H. sorenseni) are federally listed as endangered species. Research efforts to conserve and protect endangered black and white abalone have been enacted by the United States Navy Pacific Commander Fleet, the National Oceanic and Atmospheric Administration, and the California Department of Fish and Wildlife, as well as industry and non-profit stakeholders. Conservation efforts include captive breeding programs; however, determination of the reproductive state of individual abalone is notoriously difficult using traditional visual assessments. Ultrasonography is a well recognized technology used to accurately and non-lethally assess gonad reproductive condition in cultured and wild fish, and more recently cultured red abalone (H. rufescens). Here, we implemented the use of ultrasound imaging technology to monitor the gonad condition of endangered black and white abalone. Repeated ultrasound assessments of the gonad were used to assess seasonal changes in reproductive development in wild black (n=20), and captive white abalone (n=25). A modified ultrasound gonad index score was developed to incorporate multiple species of abalone. The ultrasound index scores ranged from one to five, with an index score of one being the lowest (gonad margin is thinly wrapped around the digestive gland or not present) and an index score of five being the highest (gonad margin is thick and significantly compressing the digestive gland). We show that non-lethal ultrasound imaging technology is useful for tracking cyclical changes in the gonad reproductive condition as well as more precise selection of individuals that are in peak reproductive condition. Application of ultrasound technology can provide a more accurate assessment of reproductive condition than visual gonad score without having to sacrifice an animal.